PENGARUH TEKNIK PENCUCIAN TERHADAP HASIL PEMERIKSAAN CAIRAN MANI DAN SPERMATOZOA PADA KAIN KATUN - Rizki Albizar; Mohammad Tegar Indrayana; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Sexual offence is one of social problem that often happened in society. One of the best evidence used for investigation was semen and sperm found in a victim’s dress. A dress usually made by cotton fabric. This research aimed to discover the influence of washing method to semen and sperm test result in a cotton fabric. This research planned as experimental research, used berberio test for semen and baechi test for sperm test. The result concluded that semen still visible up to 7 days, while the sperm only lasts 3 to 4 days. Conclusion there is no influence of washing found in semen test result while the washing method did influence the sperm test result in the cotton fabric. Key words: semen, sperm, cotton fabric, washing method